The use of a novel reduction plate in transoral anterior C1-ring osteosynthesis for unstable atlas fractures - Zou, Xiaobao; Yang, Haozhi; Deng, Chenfu; Fu, Suochao; Chen, Junlin; Ma, Rencai; Ma, Xiangyang; Xia, Hong (Frontiers in Surgery, 2023)
Background: Transoral anterior C1-ring osteosynthesis has been reported as an effective treatment for unstable atlas fracture, which aims to preserve important C1–C2 motion. However, previous studies have shown that the anterior fixation plates used in this technique were not suitable for the anterior anatomy of the atlas and lacked an intraoperative reduction mechanism. Objective: This study aims to evaluate the clinical effects of a novel reduction plate used in transoral anterior C1-ring osteosynthesis for unstable atlas fractures. Methods: 30 patients with unstable atlas fractures treated by this technique from June 2011 to June 2016 were included in this study. The patients' clinical data and radiographs were reviewed, and the reduction of the fracture, internal fixation placement, and bone fusion were assessed using pre- and postoperative images. The patients' neurological function, rotatory range of motion, and pain levels were evaluated clinically during follow-up. Results: All 30 surgeries were successfully performed, and the average follow-up duration was 23.5 ± 9.5 months (range 9–48 months). One patient suffered atlantoaxial instability during the follow-up and was treated with posterior atlantoaxial fusion. The remaining 29 patients had satisfactory clinical outcomes, with ideal fracture reduction, good screw and plate placement, well-preserved range of motion, neck pain alleviation and solid bone fusion. There were no vascular or neurological complications during the operation or follow-up. Conclusions: The use of this novel reduction plate in transoral anterior C1-ring osteosynthesis is a safe and effective surgical option in the treatment of unstable atlas fractures. This technique offers an immediate intraoperative reduction mechanism, which provides satisfactory fracture reduction, bone fusion, and preservation of C1–C2 motion.